PERAN PENGASUH SANTRI DALAM MENCEGAH TERJADINYA BULLYING DI PONDOK PESANTREN MUHAMMAD BASIUNI IMRAN TAHUN PELAJARAN 2024-2025 - Rani Rani; Ahmad Rathomi; Muspian (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to describe the forms of bullying among students in the environment of Pondok Pesantren Muhammad Basiuni Imran Sambas, the role of caregivers in addressing and preventing student bullying, and the factors that contribute to the occurrence of bullying in the pesantren. This research employed a qualitative approach with a descriptive research design, using interviews, observations, and documentation as data collection techniques. The data were analyzed to examine the role of caregivers in preventing bullying among students at Pondok Pesantren Muhammad Basiuni Imran Sambas during the 2024-2025 academic year. The findings indicate that the forms of bullying that occur consist of physical bullying and verbal bullying, which represent a complex phenomenon that is not always visible to pesantren caregivers. The large number of students and the variety of pesantren activities managed by caregivers often allow bullying practices to escape supervision. Furthermore, caregivers play a crucial role in addressing bullying through their functions as mu’allim (educator), mu’addib (supervisor and moral guide), and murabbi (role model), and they are authorized to take immediate actions to respond to bullying behavior in order to prevent violence within the pesantren environment. Additionally, the factors causing bullying include individual factors and group influence factors; therefore, bullying prevention must be carried out comprehensively, not only by improving individual behavior but also by creating a safe, caring social environment that rejects all forms of violence.